Evidence for the involvement of ACC deaminase from Pseudomonas putida UW4 in the biocontrol of pine wilt disease caused by Bursaphelenchus xylophilus - Nascimento, Francisco (2013)
Abstract Pine wilt disease, caused by the nematode Bursaphelenchus xylophilus, is responsible for devastation of pine forests worldwide. Until now, there are no effective ways of dealing with this serious threat. The use of 1-aminocyclopropane-1-carboxylate (ACC) deaminase (encoded by the acdS gene)-producing plant growth-promoting bacteria has been shown to be a useful strategy to reduce the damage due to biotic and abiotic stresses. Pinus pinaster seedlings inoculated with the ACC deaminase-producing bacterium Pseudomonas putida strain UW4 showed an increased root and shoot development and reduction of B. xylophilus induced symptoms. In contrast, a P. putida UW4 acdS mutant was unable to promote pine seedling growth or to decrease B. xylophilus induced symptoms. This is the first report on the use of ACC deaminase-producing bacteria as a potential biological control agent for a tree disease, thus suggesting that the inoculation of pine seedlings grown in a tree nursery might constitute a novel strategy to obtain B. xylophilus resistant pine trees.